Group B Streptococcus Infections in Non-Pregnant Adults, Italy, 2015–2019 - Monica Imperi; Giovanni Gherardi; Giovanna Alfarone; Roberta Creti (Pathogens, 2024)
Group B Streptococcus (GBS, Streptococcus agalactiae) is a pathogen of increasing importance in adults. Severe and invasive cases in non-pregnant adults were collected during the period 2015–2019 by voluntary-based surveillance. In total, 108 GBS strains were phenotypically and genotypically characterized for the serotype, antimicrobial resistance, pili, surface protein genes, and the hyper-virulent adhesin hvgA. Patients were divided into two age groups: adults (18–64 years; n = 32) and older adults (≥65 years; n = 72). The average age was 70.8 years, with a male/female ratio of 1.7. Most isolates were recovered from cases of bacteremia (blood, n = 93), and a higher frequency of invasive GBS infections (iGBS) was found among older adults (66.7%). Serotype III was the most frequent (n = 41, 38%), followed by type Ia and type V (n = 20 each, 18.5%). Serotypes Ia, Ib, II, III, IV, and V accounted for all but one isolates (99.1%). The iGBS isolates were universally susceptible to penicillin, while the prevalence of resistance to clindamycin, erythromycin, tetracycline, and high-level gentamicin resistance was 26.8%, 24.1%, 85.2%, and 5.5%, respectively, with the predominance of the erm(B) gene for macrolide resistance and the tet(M) gene for tetracycline resistance. The associations between the serotypes/antimicrobial resistance/virulence traits underlined the increasing importance of serotype III and its contribution to antimicrobial resistance as well as the steady increase over time of serotype IV. This nationwide study confirmed the need for monitoring the GBS epidemiology in non-pregnant adults through continuous surveillance of GBS infections.